Leadership Styles of School Leaders and the Mental Health of Teachers in a university in Beijing, China - YUE, ZHENFANG (Pacific International Journal, 2024)
This study explores the relationship between leadership styles exhibited by school leaders at Beijing University for Business Administration (BUBA) and the mental health of its teaching staff. BUBA, founded in 1994, has been dedicated to providing quality education for over 20 years and has received recognition and support from various sectors. The importance of teacher mental health in the teaching profession is emphasized, as teachers play a multifaceted role beyond imparting knowledge, impacting student outcomes and the overall quality of education. Teacher well-being is closely linked to student learning, and recognizing the mental health challenges teachers face is vital to prevent negative consequences for both educators and students. The research problem seeks to understand the relationship between leadership styles at BUBA and teacher mental health, with objectives that include examining leadership styles, assessing teacher mental health, investigating correlations, identifying contributing factors, and providing recommendations. The research methodology employs a qualitative approach, involving interviews with 10 teachers, to gain in-depth insights. The research findings reveal a diverse range of leadership styles at BUBA, impacting teacher mental health. Collaborative and supportive leadership styles are associated with positive teacher mental health, fostering a conducive work environment. Authoritarian and directive styles, on the other hand, contribute to stress and dissatisfaction among teachers. Factors within leadership styles, such as professional development and recognition, further influence teacher well-being. Recommendations include leadership development, transparent communication channels, and strategies to reduce workload pressures and promote well-being.